High Fructose Consumption and Metabolic Syndrome from Gout Perspective - Fulden Aydın, Ümmühan; Kozanoğlu, Erkan; Tuli, Abdullah (Cerrahpaşa Medical Journal, 2024)
Abstract: Uric acid is formed as a consequence of the catabolism of purine nucleotides. The removal of uric acid from the body is mainly carried out by the kidneys via urine and, to a lesser extent, by the intestinal tract via feces. Excretion and reabsorption of uric acid from the intestinal tract, and especially from the kidneys, are carried out by special transporters. Genetic variations in these carriers have been related to increased or decreased serum uric acid levels. Uric acid synthesis increases for various reasons that increase the destruction of purine nucleotides, causing serum uric acid levels to rise. Although hyperuricemia, with a mean serum uric acid level above 6.8 mg/dL, does not always cause gout, if hyperuricemia is not kept under control, it can result in gout; an inflammatory disease characterized by the crystallization of monosodium urate. As well as non-modifiable factors such as age and ethnicity; diet, which is one of the modifiable factors, can promote gout or recurrence of gout flare-ups. Excessive consumption of products with high fructose content can cause hyperuricemia and gout. In addition, the increase in uric acid resulting from excessive consumption of fructose, and overall and sustained high serum uric acid levels have been shown to cause various disorders that will give rise to metabolic syndrome. In this review, the interwoven relationships between hyperuricemia—an increase in serum uric acid levels—and the resulting gout, as well as metabolic syndrome, and the role excessive fructose consumption plays in these, have been investigated. Cite this article as: Aydın Ü, Kozanoğlu E, Tuli A. High fructose consumption and metabolic syndrome from gout perspective. Cerrahpaşa Med J. 2024;48(2):191-196.